THE ROLE OF NIGERIA IN SHAPING THE FUTURE OF THE ECONOMIC COMMUNITY OF WEST AFRICAN STATES - Okoro, Elizabeth Nneka; Adebayo, Ibrahim Tunde; Nwosu , Chiamaka Blessing (Ayden Journal of Management and Social Sciences, 2024)
Expectedly, forty-nine years since the establishment of Economic Community of West African States (ECOWAS), there has been significant transformation in West African socioeconomic and political integration. Nonetheless, very recent developments in West Africa indicate a retreat in integration arrangements; most evidently, the resurgence of military rule in some member countries, followed by threats of withdrawal from ECOWAS. Invariably, there appears to be a mismatch between the level of institutional transformation and the extent of integration. As a matter of policy and multilateral exigency, Nigeria played a leading role in the formation of the Economic Community of West African States (ECOWAS) in 1975. In view of Nigeria’s dominant posture, and underlying challenges, a more concerted effort from Nigeria would guarantee a genuine integration of West Africa. This research therefore examines how Nigeria advanced the course of regional integration and the prospects thereof. Data from Primary and Secondary sources was analysed using the descriptive method. Dependency Theory was adopted to explain the enduring external strains on integration initiatives. Findings indicate that West African integration must correspond with transformation in democratic principles and practices, beginning with Nigeria, the dominant member, and extending to others.